DEVELOPING RICH LANGUAGE LEARNING ENVIRONMENT MATERIAL TO SUPPORT LITERACY SKILLS OF THE FOURTH GRADE STUDENTS OF PRIMARY SCHOOLS IN BALI PROVINCE - Dian Pondika C, Ni L. G.; Artini, Luh Putu; Marhaeni, A.A.I.N. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
Abstract This study aimed at developing rich language learning materials to support literacy skills of grade 4 students in Bali province. Research and Development (R&D) design was employed in this study. There were 6 primary schools involved and the data were collected through document study, observation, questionnaire, and test. The findings show that the literacy coverage of English language learning for grade 4 students includes reading simple descriptive texts and writing simple and meaningful descriptive sentence. The rich language learning environment (RLLE) material were developed in various texts such as topical vocabulary, grammar focus, everyday expression, language game, and stories need to be developed. The quality of the developed RLLE material is good based on the result of the expert jugdments and the result of questionnaires. The RLLE material was effective to support grade 4 students?  literacy skills based on the result of statistical analysis on the literacy skills. The post-test result was significantly higher than the pre-test scores. Thus, the RLLE material is recommended to be used as suplementary material to support students? literacy skills of grade 4 in Balinese elementary schools. Keywords : rich language learning environment, literacy skills, young learner